Analysis Of Business Income Of Tofu Industry Production In North Labuhanbatu District - Tri Rahayu; Muhammad Ali Ihsan; Marlina Siregar (UNIVED Press, 2023)
As time goes by, tofu continues to be popular because it is an important menu item and a source of protein and is safe for consumption by all age groups at a relatively cheap price. The market potential for tofu is quite large and continues to grow along with the development of the food and culinary business. The aim of this research is to analyze the income of the tofu making business in North Labuhan Batu, the amount of production costs incurred and revenues. This research uses quantitative methods and primary and secondary data types. There are approximately 50 tofu production businesses in North Labuhan Batu and 10 businesses were sampled. The results of the research show that the total income from the tofu production business in North Labuhan Batu is IDR 116,482,000/month, with revenues of IDR 248,789,000 with a total production cost of IDR 130,122 from the tofu production business. 000/Month. And can produce a maximum of up to 1,300 boards/month. The highest monthly profit from the tofu production business in North Labuhan Batu is IDR 18,125,000 with total costs of IDR 19,765,000, with revenues of IDR 37,765,000. However, all tofu production businesses in North Labuhan Batu make a profit and do not experience losses, meaning that tofu production businesses in the North Labuhan Batu